Role of endothelial cells in graft-versus-host disease - Neidemire-Colley, Lotus; Robert, Jérémy; Ackaoui, Antoine; Dorrance, Adrienne M.; Guimond, Martin; Ranganathan, Parvathi (Frontiers in Immunology, 2022)
To date, the only curative treatment for high-risk or refractory hematologic malignancies non-responsive to standard chemotherapy is allogeneic hematopoietic transplantation (allo-HCT). Acute graft-versus-host disease (GVHD) is a donor T cell-mediated immunological disorder that is frequently fatal and the leading cause of non-relapse mortality (NRM) in patients post allo-HCT. The pathogenesis of acute GVHD involves recognition of minor and/or major HLA mismatched host antigens by donor T cells followed by expansion, migration and finally end-organ damage due to combination of inflammatory cytokine secretion and direct cytotoxic effects. The endothelium is a thin layer of endothelial cells (EC) that line the innermost portion of the blood vessels and a key regulator in vascular homeostasis and inflammatory responses. Endothelial cells are activated by a wide range of inflammatory mediators including bacterial products, contents released from dying/apoptotic cells and cytokines and respond by secreting cytokines/chemokines that facilitate the recruitment of innate and adaptive immune cells to the site of inflammation. Endothelial cells can also be damaged prior to transplant as well as by alloreactive donor T cells. Prolonged EC activation results in dysfunction that plays a role in multiple post-transplant complications including but not limited to veno-occlusive disease (VOD), transplant associated thrombotic microangiopathy (TA-TMA), and idiopathic pneumonia syndrome. In this mini review, we summarize the biology of endothelial cells, factors regulating EC activation and the role of ECs in inflammation and GVHD pathogenesis.